Quality of Service Based Vertical Handoff in Heterogeneous Wireless Networks - Kumar, Rajiv (My University, 2014)
The increasing demand of continuous end-to-end connectivity and the user desire for quality of service (QoS), while moving between different accesses technologies is a major challenge in heterogeneous wireless access networks. The issue in heterogeneous networks is to allow vertical handoff between pairs of different types of networks in the presence of Second Generation (2G), Third Generation (3G), Wireless Local Area Network (WLAN), Wireless Metropolitan Area Network (WMAN), satellite and Fourth Generation (4G) networks. The vertical handoff decision becomes critical when it is required for certain set of Quality of Service (QoS). In this thesis, we have proposed an optimum and QoS based vertical handoff decision algorithms for heterogeneous networks. We have considered handoff between WLAN to Universal Mobile Telecommunications System (UMTS), WiMAX to UMTS and UMTS-WiMAX. The QoS concept encapsulates the idea that different data streams could be treated differently by the network depending upon the service being carried. QoS feature provides the required performance of latency, jitter and packet loss needed to support the service. In the proposed work, a swarm based technique has been proposed for improving the QoS metrics for WLAN/UMTS/WiMAX networks. Swarm based technique is used to find out the best network in advance. A combined cost function is estimated by using the battery lifetime along with the metrics like Network Load, Data Rate, Received Signal Strength (RSS) and Signal-to Noise Ratio (SNR). The handoff is then executed by the serving Base Station (BS) that evaluates these QoS metrics to find a set of candidate target networks with demand of optimum QoS level. Based on analysis and comparison of results obtained with simulation work, it has been observed that proposed algorithm reduces the jitter, delay and improves QoS parameters.
PHD, ECED
Keywords: QoS, Vertical handover, Hetrogenous netwroks